AGAMA DALAM PERUBAHAN SOSIAL MASYARAKAT - Elviana, Isa; Widy pramesty, Widy (TANDA, 2022)
The role of religion is very important for human life in this world to achieve happiness in this world and happiness in the afterlife. Religion or faith in divine power also has a very important role in human life. Religion provides balance and order for society amidst the social changes that influence it, religion functions to protect against evil and directs the better above all else. Religion has teachings that are very important for the overall outlook of society and its functioning. Religion is present in human life with a more functional approach as a social bond, fostering a sense of solidarity, strength, family relationships, creating peace and functioning as social control, changing life for the better to achieve salvation in this world and the hereafter, and a series of roles which are all aimed at maintaining social balance in society.